Effect of degree of crystallographic texture on ferro‐ and piezoelectric properties of Ba0.85Ca0.15TiO3 piezoceramics. Issue 5 (3rd March 2017) - Schultheiß, Jan; Clemens, Oliver; Zhukov, Sergey; von Seggern, Heinz; Sakamoto, Wataru; Koruza, Jurij
Abstract: Crystallographic texturing is a promising approach to reduce the performance gap between randomly oriented polycrystalline piezoelectrics and perfectly oriented single crystals. Here, the influence of the degree of crystallographic texture on the electromechanical properties and their temperature stability of the lead‐free perovskite ferroelectric Ba0.85 Ca0.15 TiO3 is investigated. Samples with a broad range of (100), (001) crystallographic texture (Lotgering factor 26%‐83%) were prepared by the reactive templated grain growth method. Crystallographic and microstructural analysis have been carried out using X‐ray diffraction and scanning electron microscopy, while the temperature‐dependent electromechanical properties were characterized by dielectric, piezoelectric, polarization, and strain measurements. It was revealed that the total bipolar strain and the coercive field are linearly dependent on the Lotgering factor. The total bipolar strain increased by 80%, whereas the coercive field decreased by 18% due to crystallographic texturing. Likewise, the temperature stability of the electromechanical properties of the samples was found to be dependent on the degree of texture. A sample with a high degree of texture exhibited a Curie temperature of 117°C, which is 21% higher compared to a counterpart with a low degree of texture. This was related to chemical inhomogeneity and a modified internal mechanical stress state.